Impact of sulphur dioxide on root colonization by VAM fungi and nodulation on blackgram - M. WAJID KHAN, MADHU KULSHRESHTHA and (Indian Phytopathology, 2002)
The impact of sulfur dioxide on Glomus caledonium and Rhizobium sp. on Vigna mungo roots was investigated in Aligarh, Uttar Pradesh, India. It was demonstrated that root symbionts minimize the negative effects of sulfur dioxide.